The floppy infants and metabolic causes - Dorum, Sevil; Dorum, Bayram Ali (The European Research Journal, 2020)
Objectives: To describe the clinical, metabolic and genetic characteristics of the floppy infants diagnosed at a tertiary care center.Methods: A retrospective analysis was performed on the medical files of 90 floppy infants diagnosed in the pediatric metabolism department of our tertiary care center. Baseline descriptives, prenatal and perinatal data, results of genetic and metabolic tests as well as neuroradiological imaging findings were overviewed.Results: Our series was comprised of 42 (46.7%) females and 48 (53.3%) males. Consanguineous marriages were detected in 60 (66.7%) cases. There was no history of prenatal comorbidity or birth-related trauma or infections. Gestational age was ≥ 37 weeks in 78 (87%) infants. The average body weight was 2521.2 ± 839.4 grams (range: 1510-4300). The average height and head circumference were 48.9 ± 0.9 cm and 33.9 ± 0.7 cm, respectively. The etiology of hypotonia was found to be central in 89 (98.8%) infants. The most frequent diseases diagnosed were vitamin B12 deficiency (14.4%), dystrophinopathy (7.7%), spinal muscular atrophy (5.5%), gangliosidosis (3.3%), peroxisomal disease (3.3%), Pompe disease (3.3%), and Zellweger disease (3.3%).Conclusions: The floppy infant still constitutes a diagnostic challenge in spite of the technological advances in genetic, molecular and metabolic test methods. The priority and selection of diagnostic measures need to be determined on an individualized basis, and multidisciplinary and collaborative work is mandatory to set the diagnosis cost-effectively without delay. An algorithm based and individualized approach may provide a high diagnostic yield for the clinician.